HARMONY AND HEALTH: APPROACH TO IDENTIFYING RISK FACTORS AND COMPLICATIONS OF DIABETES MELLITUS - Dina Rahma Fadlilah; Irna Hasanah; Sadya Bustomi; Abul A'la Al Maududi (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Diabetes mellitus, commonly referred to as diabetes, is a chronic condition characterized by lifelong affliction. This study employs the literature review methodology, wherein researchers undertake a systematic examination of a range of current publications encompassing diverse genres. The objective of this study is to explore diverse concepts and theories that can subsequently be formed to align with the research objectives. Diabetes mellitus (DM) is a chronic metabolic condition with several causes, characterized by elevated blood glucose levels and associated metabolic dysregulation of carbohydrates, lipids, and proteins due to insufficient insulin activity. Diabetic foot is recognized as a notable consequence of diabetes mellitus. The management of diabetic foot can be improved with the implementation of foot workouts. Typically, individuals diagnosed with diabetes mellitus have access to several treatment options, including insulin therapy, administration of diabetic medications, exploration of alternative treatments, consideration of surgical interventions, and adoption of a healthier lifestyle.